WHAT WILL HAPPEN TO NUMBER OF THE INFECTED IF ACCURACY OF THE PCR TEST IMPROVES? - Fujita, Yasunori (International Journal of Research -GRANTHAALAYAH, 2021)
Among the strategies to tackle the COVID-19, much attention is paid to “test and isolation” advocated by Romer (2000), Peto et al (2020) etc., in addition to vaccination and development of medicines to treat COVID-19. According to these articles, what is necessary is a targeted version of lockdown, that is, to test everyone regularly and isolate the small fraction of the population who test positive. There is, however, concern that the PCR test is not always effective, so that, in the present paper, we investigate the effects of improvement of the PCR test by constructing a simple intertemporal theoretical model. Main result we obtain is that improvement of the PCR test could increase the number of the infected individuals at first, so that we should improve the accuracy of the PCR test much enough to reduce the number of the infected individuals.